Horse-rider interaction in dressage riding - Münz, A.; Eckhardt, F.; Witte, K. (Human Movement Science, 2014)
In dressage riding the pelvis of the rider interacts with the horse physically. However, there is little information about the influence of riding skill on the interaction of the human pelvis with the horse. Therefore this paper aims to study the interaction between horse and rider in professional riders (PRO) and beginners (BEG). Twenty riders rode in walk, trot, and canter in an indoor riding hall with inertial sensors attached to their pelvis and to the horses` trunk. Statistical analysis of waveform parameters, qualitative interpretation of angle-angle plots, and cross-correlation of horse and rider were applied to the data. Significant differences between PRO and BEG could be found for specific waveform parameters. Over all gaits PRO kept their pelvis closer to the mid-position and further forward whereas BEG tilted their pelvis further to the right and more backwards. The coupling intensity of horse and rider revealed differences between the gaits. Furthermore phase shifts were found between PRO and BEG. This paper describes a sensor-based approach for the investigation of interactions of the human pelvis with the trunk of a horse under in-field conditions. First the results show that the riding level influences the posture of a rider and secondly that differences can be detected with contemporary available sensor technology and methods.